Atitudes ambientais e energias alternativas: uma explicação pautada em valores - Fonseca, Felicíssimo Bolívar da (2013)
This research aims at knowing to what extend the environmental attitudes may be predicted in terms of the human values and in relation to the person-environment relationships. More especially it is intended to know how the human values and person- nature relationships explain the pro environmental attitudes that promote the sustainable use of natural resources having as focus the production and consume of energy. In this sense, the theoretical approach highlights themes concerning conventional and alternative energy use, besides of the values constructs, attitudes of preservation and environmental inclusion. Two studies were carried out. The study 1 aimed at knowing how the environmental attitudes were correlated with human values, the attitudes towards the conventional and solar attitudes and the connectivity with environmental inclusion. This study counted on a non probability convenience sample of 307 participants came from the general population (63%) and students from Environmental Technology Course offered by IFMT- Campus Cuiabá - Bela Vista and Forestry Engineering Course given by UFMT, Cuiabá (MT). The subjects ages varied between 18 and 85 years (m =30, 8, sd = 14.43), the majority was female (62%). The participants answered the following research instruments: Environmental attitudes inventory, Environmental Connectivity Scale, Solar Energy Attitudes Scale, Conventional Energy Attitudes Scale, Basic Values Questionnaire, Social Desirability Scale and sociodemographic questions. The results indicated that participants are concerned about the environment; they had positive attitudes towards to sustainable energy sources, besides of revealing the feeling of being included to the natural environment. Concerning the super-personal values, these were positively correlated with preservation attitudes, while the social values did it with those of utilization. The attitudes towards solar energy were positively correlated with the preservation attitudes, but those concerning the conventional energy did it negatively, and finally, consistent with the previous result, the attitudes towards solar energy were positively correlated with environmental connectivity and inclusion. It was observed an opposite pattern towards conventional energy attitudes. The Study 2 aimed at replicating the findings described above. In this sense, this study counted on a non probability convenience sample of 175 participants from the general population of the cities of Cuiabá and Barão de Melgaço. Their ages were between 18 and 92 years (mean = 37.7, sd =14,43), the majority was female (62%). These participants answered the same questionnaires above described. In general, it was observed the same results of Study 1. It was evidenced that the participants of Barão de Melgaço, despite of having the prevalence of daily activities associated to the natural environment, they presented lower propensities to environmental protection and care behaviors when compared to participants from the capital city. In conclusion, the attitudes of environmental preservation, as well as, the environmental connectivity and inclusion may be important to explain attitudes towards solar and conventional energy, in this sense, the human values, especially the super-personal; values had the leading role in this context. It is trust, then, that this thesis represents an important contribution to the literatures of Social Psychology and Environmental Psychology, offering opportunities for considering future researches, mainly, contributing to the public policies in order to ensure environmental education and promote environmentally sustainable behaviors.